Diversity of Insects Associated with Stingless Bee Lepidotrigona terminata at Plantations in Batu Gadang Village, Padang Pariaman Regency, West Sumatra. Issue 1 (1st July 2022) - Afriana, R; Dahelmi,; Herwina, H; Janra, M N; Jasmi,
Abstract: The study observed the diversity of insects that supposed to have direct association with stingless bee Lepidotrigona terminata within plantation habitats in Batu Gadang Village, Padang Pariaman Regency in West Sumatra Province. This study had been conducted from March to May 2021 and aimed to identify insect species that used similar resources with stingless bees Lepidotrigona terminata bred at meliponiculture activity in this area. It used purpossive sampling method by establishing three plant species that frequently visited by the stingless bee as focal of observation, namely jengkol of bitter bean ( Archidendron pauciflorum ), coconut ( Cocos nucifera ) and kepundung ( Baccaurea racemosa ). A total of eight insect species collected from these plants; they are classified into five families and four orders. The ant Oecophylla sp. (Hymenoptera, Formicidae) with 21 individuals became insect that mostly interacted with the stingless bees while Coreus marginatus (Hemiptera, Coreidae) and Chrysolina sp. (Coleoptera, Chrysomelidae) were the least. While specific interaction they made with stingless bee Lepidotrigona terminata needs further investigation, these insects have associated to the least with the stingless bee at the observed plant species.